A procedural and object-oriented statistical language - Ikunori Kobayashi; Takeshi Fujiwara; Junji Nakano; Yoshikazu Yamamoto (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2001)
A language of a statistical system is important, even though it bas an effective graphical user interface. A language may be used to control the statistical system at will and to implement new statistical procedures which are not realized in the system at the beginning. This paper introduces the features and the syntax of the language of the statistical system Jasp (Java based statistical processor). We use a procedural function-based script 1anguage Puuts as the basis of the language, and add object-oriented mechanism thinking much of ease, flexibility and extendibility.
urn:nbn:de:kobv:11-10050373
Keywords: 330; Jasp; Java; Object-Oriented Language; Procedural Language; Statistical system